Percutaneous microchannel unilateral approach bilateral micro decompression for adjacent segmental degeneration after lumbar fusion at 10 years: a case report and review of literature - Zhang, Tingxin; Gao, Gang; Gao, Feng; Guo, Nana; Wang, Yongjiang (Frontiers in Surgery, 2024)
Background: Adjacent segmental degeneration after lumbar fusion is one of the common long-term complications after lumbar fusion. With the continuous development of adjacent segmental degeneration, patients who fail conservative treatment often need reoperation to relieve symptoms. In recent years, the technique of bilateral microdecompression through unilateral approach under microchannel has been widely used in the treatment of lumbar degenerative diseases. However, the efficacy of this procedure for adjacent-segment degeneration after lumbar fusion has not been established. Here, we report a case of bilateral microscopic decompression via a unilateral approach through a microchannel in a patient with adjacent segmental degeneration after lumbar fusion.Case report: A 70-year-old male patient was admitted to hospital because of lumbago accompanied by left lower extremity pain, numbness and weakness for 2 years, which aggravated for 2 months. Ten years ago, he underwent PLIF for lumbar spinal stenosis, and recovered well after the operation.According to imaging data and physical examination, the diagnosis was adjacent segmental degeneration after lumbar fusion. Bilateral microdecompression was performed through a unilateral approach under a microchannel. Good clinical outcomes was observed through one-year postoperative follow-up.This report reports the successful treatment of a patient with ASD 10 years after lumbar fusion. Bilateral microdecompression via a unilateral approach under a microchannel is a safe and effective method for the treatment of ASD after lumbar fusion with good surgical outcomes.